Genomic Insights Into Cadmium Resistance of a Newly Isolated, Plasmid-Free Cellulomonas sp. Strain Y8 - Chen, Jinghao; Wang, Likun; Li, Wenjun; Zheng, Xin; Li, Xiaofang (Frontiers in Microbiology, 2022)
Our current knowledge on bacterial cadmium (Cd) resistance is mainly based on the functional exploration of specific Cd-resistance genes. In this study, we carried out a genomic study on Cd resistance of a newly-isolated Cellulomonas strain with a MIC of 5 mM Cd. Full genome of the strain, with a genome size of 4.47M bp and GC-content of 75.35%, was obtained through high-quality sequencing. Genome-wide annotations identified 54 heavy metal-related genes. Four potential Cd-resistance genes, namely zntAY8, copAY8, HMTY8 and czcDY8, were subjected to functional exploration. Quantitative PCR determination of in vivo expression showed that zntAY8, copAY8 and HMTY8 were strongly Cd-inducible. Expression of the three inducible genes against time and Cd concentrations were further quantified. It is found that zntAY8 responded more strongly to higher Cd concentrations, while expression of copAY8 and HMTY8 increased over time at lower Cd concentrations. Heterologous expression of the four genes in Cd-sensitive Escherichia coli led to different impacts on hosts’ Cd sorption, with an 87% reduction by zntAY8 and a 3.7-fold increase by HMTY8. In conclusion, a Cd-resistant Cellulomonas sp. strain was isolated, whose genome harbors a diverse panel of metal-resistance genes. Cd resistance in the strain is not controlled by a dedicated gene alone, but by several gene systems collectively whose roles are probably time- and dose-dependent. The plasmid-free, high-GC strain Y8 may provide a platform for exploring heavy metal genomics of the Cellulomonas genus.